Investigação sobre a formação de espécies de arsênio orgânico em soluções de nutrição parenteral - Mörschbächer, Vanessa Domingues (2006)
Parenteral nutrition is the nutrients administration by intravenous mean in patients who cannot consume them for gastrointestinal way. Parenteral Nutrition Solutions are stored in glass and plastic containers, being the glass the most used due to its rigid structure, chemical resistance, sterilization easiness and transparency. Among glass constituents is the arsenic, in form of As2O3, used as refining agent to promote bubbles removal generated in the casting one. Arsenic is highly toxic. Its toxicity however is not dependent on its concentration only,but on its chemical form. Among inorganic species, arsine (AsH3) is more toxic than arsenite (As(III)) which is, more toxic than the arsenate (As(V)). Arsenic is methylated in the organism alternating the oxidation state of arsenic pentavalent the trivalent. The methilation is known as a detoxification mechanism, but studies have been shown that forms of MMA and DMA may be as mutagenic, carcinogenic and cytogenic as the forms of inorganic arsenic, or even more. Studies have been shown that most substances used in parenteral formulations, as: salts, amino acid, glucose and vitamins, can present Arsenic (As(III and As(V)) as contaminant. The species of Arsenic (As(III) and As(V)) can be present in the raw material or be leached from glass containers by different mechanisms, being the sterilization process the determinative factor for that this to occur. Despite toxicological implications around the presence of species of Arsenic in these formulations it important to investigate the possible transformation of the species of arsenic during the sterilization process of parenteral nutrition solutions. In this work, it was investigated the possibility of formation of organic arsenic species (DMA(V) and MMA(V)), due to methilation reaction of the arsenic inorganic species for reaction with the organic species of parenteral nutrition solutions. The arsenic species separation (DMA(V), MMA(V) and As(V)) was carried out by ionic chromatography, and the quantification by hydride generation atomic absorption spectrometry. Due to the complex nature of the matrix constituent the direct injection of the samples in the chromatographic system was not possible, being necessary, therefore, a "clean up" step was developed. The sterilization procedure was carried out with solutions of amino acids, glucose and vitamins, with addition of inorganic arsenic species. The comparison of the results between sterilized and not sterilized solutions showed that arsenic organic species (DMA(V) and MMA(V)) were not formed in solution. The arsenic speciation analysis (As(III), DMA(V), MMA(V) and As(V)) in commercial solutions of parenteral nutrition showed that if they contain organic arsenic, the concentration is very low, being lesser than the limit for arsenic allowed by pharmacopeias.